Chemistry of Diruthenium and Dirhodium Analogues of Pentaborane(9): Synthesis and Characterization of Metal N, S‐Heterocyclic Carbene and B‐Agostic Complexes. Issue 9 (23rd December 2014) - Roy, Dipak Kumar; Mondal, Bijan; Anju, R. S.; Ghosh, Sundargopal
Abstract Building upon our earlier results on the synthesis of electron‐precise transition‐metal–boron complexes, we continue to investigate the reactivity of pentaborane(9) and tetraborane(10) analogues of ruthenium and rhodium towards thiazolyl and oxazolyl ligands. Thus, mild thermolysis of nido‐[(Cp*RuH)2B3H7] (1) with 2‐mercaptobenzothiazole (2‐mbtz) and 2‐mercaptobenzoxazole (2‐mboz) led to the isolation of Cp*‐based (Cp*=η5‐C5Me5) borate complexes 5 a, b [Cp*RuBH3L] (5 a: L=C7H4NS2; 5 b: L=C7H4NOS)) and agostic complexes 7 a, b [Cp*RuBH2(L)2], (7 a: L=C7H4NS2; 7 b: L=C7H4NOS). In a similar fashion, a rhodium analogue of pentaborane(9), nido‐[(Cp*Rh)2B3H7] (2) yielded rhodaboratrane [Cp*RhBH(L)2], 10 (L=C7H4NS2). Interestingly, when the reaction was performed with an excess of 2‐mbtz, it led to the formation of the first structurally characterized N, S‐heterocyclic rhodium‐carbene complex [(Cp*Rh)(L2)(1‐benzothiazol‐2‐ylidene)] (11) (L=C7H4NS2). Furthermore, to evaluate the scope of this new route, we extended this chemistry towards the diruthenium analogue of tetraborane(10), arachno‐[(Cp*RuCO)2B2H6] (3), in which the metal center possesses different ancillary ligands.